2008
DOI: 10.1002/pi.2475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of montmorillonite modification on the behaviour of polyamide/polystyrene blends

Abstract: BACKGROUND: In nanocomposites with multiphase matrices, the addition of layered silicate not only has a reinforcing effect, but also changes significantly the morphology, namely the size and the structure of the dispersed phase. In this paper, we focus on systems with polyamide 6 (PA6)/polystyrene (PS) matrices. The effect of clay was studied over the whole composition range together with the simultaneous variation of basic parameters influencing the structure and mechanical behaviour, i.e. the clay treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The compatibilizing effect and resulting properties are determined by the clay localization and degree of dispersion, which is strongly influenced by the clay-polymer affinity. A marked effect of clay on the refinement of the dispersed phase was found when the clay was present in the matrix phase and at the interface, limiting coalescence due to an active interfacial role of the clay [58]. The observed morphology refinement could be due to the modification of the viscosity ratio between both polymers in the blend [28].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The compatibilizing effect and resulting properties are determined by the clay localization and degree of dispersion, which is strongly influenced by the clay-polymer affinity. A marked effect of clay on the refinement of the dispersed phase was found when the clay was present in the matrix phase and at the interface, limiting coalescence due to an active interfacial role of the clay [58]. The observed morphology refinement could be due to the modification of the viscosity ratio between both polymers in the blend [28].…”
mentioning
confidence: 88%
“…The best reinforcement effect was observed for stearylamine modified MMT (S-MMT) due to its longest alkyl chains, largest basal spacing, and better exfoliation in the PA6/PP matrix. Kelnar et al [58] reported the effect of montmorillonite modification on the behavior of PA/PS blends. The results indicated that nanosilicates can effectively influence the structure of PA/PS blends.…”
Section: 3mentioning
confidence: 99%
“…The enhanced efficiency of impact modifiers allows their content to be reduced. This effect was observed in both immiscible thermoplastic systems [7][8][9] and epoxies with two phase structures formed by the reaction-induced phase separation (RIPS) [10] of a modifier dissolved in an uncured resin. The enhanced mechanical performance of epoxy systems was mostly observed in liquid rubbers and clays [11][12][13] and in combinations of thermoplastics (PEEK, PEI, PES, ABS) and clays [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 95%
“…The primary shortcoming is the increase in viscosity that limits the content of the modifier. An increasing number of studies have indicated not only that nanofillers (NF) can compensate for the stiffness reduction of impact-modified polymeric systems but also that a suitable combination of NF and a polymeric modifier can also provide a synergistic effect (e.g., further increasing the material toughness) [7][8][9][10][11][12][13][14][15][16]. The enhanced efficiency of impact modifiers allows their content to be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The embrittling effect may be due to the weak interfacial adhesion between the clay platelets and the polymer matrix [28] the maximum toughness at a clay conc. of 5wt% is also reported for Nylon6-PS blends [29]. Ductility tends to reduced at higher filler loading [30].…”
Section: Impact Propertiesmentioning
confidence: 53%